Digital Marketing as a Vehicle for Promotion and Sales of Products At Shopee Avero Official Shop - Iryanti, Endang; Maharani, Rahma Aprilia (East Asian Journal of Multidisciplinary Research, 2024)
In the current era of advanced digitalization, product marketing and sales have gone through very rapid changes. The development of information and communication technology has opened new pathways for various new opportunities in the world of business processes. One of them is the emergence of digital marketing innovation, which has become a forum for business processes for promoting and selling products on various online platforms. In the industrial era 4.0, everyone is required to use technology in all fields. This changes the socio-economic lifestyle, and the type of work one wants to achieve also changes significantly. All types of transactions use non-cash and self-service facilities. This happens in all transactions, for example in online trading, transportation, insurance, and many more. This research aims to determine the use of Digital Marketing through E-Commerce. The method in this research is a qualitative descriptive method by looking for data sources from research results and news whose truth is acknowledged. The research results state that the most widely used e-commerce is Shopee. The existence of an e-commerce platform helps people carry out buying and selling transactions anywhere and anytime.